G-CBT for Reducing Depression Symptoms in Individuals from Dysfunctional Family - Pramadani, Arti; Retnowati, Sofia (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2024)
Individuals from dysfunctional family have various risks of mental health deterioration including depression. To solve this family problem actually it is the best to conduct family therapy to the family. But unfortunately not all dysfunctional family are willing to cooperate in family therapy. Therefore individual therapy is considered important to protect individual of dysfunctional family from depression. The aim of this research is to examine the effectivity of Gratitude Cognitive Behavior Therapy in reducing depressive simptoms in individuals from dysfunctional family. Method used in this research is single case quasy experiment with A-B-A design. Findings from this research tells us that G-CBT is efective in reducing depression in individuals from dysfunctional family. Participants get some positive effect of this intervention including wider perspective, ability to see other points of view, appreciate every positive little thing, acknowlede one’s strenght, and increase sense of gratitude to God.